2023
DOI: 10.3390/medicina59020306
|View full text |Cite
|
Sign up to set email alerts
|

Morphopathogenesis of Adult Acquired Cholesteatoma

Abstract: Background and Objectives. The aim of this study was to compare the distribution of proliferation markers (Ki-67, NF-κβ), tissue-remodeling factors (MMP-2, MMP-9, TIMP-2, TIMP-4), vascular endothelial growth factor (VEGF), interleukins (IL-1 and IL-10), human beta defensins (HβD-2 and HβD-4) and Sonic hedgehog gene protein in cholesteatoma and control skin. Methods. Nineteen patient cholesteatoma tissues and seven control skin materials from cadavers were included in the study and stained immunohistochemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…It is accepted to transform percentages into “+” values and numbers for statistical purposes. The semi-quantitative method and scoring system levels used in this research are well established and were widely used in previous morphological studies for several decades [ 26 , 27 ], and are still used and accepted in recent publications [ 28 , 29 ]. The appearance of positive structures was recorded using a semi-quantitative method where: 0—no positive structures in the visual field; 0/+—occasional positive structures in the visual field; +—few positive structures; ++—a moderate number of positive structures; +++—numerous positive structures; ++++—abundant positive structures in the visual field [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is accepted to transform percentages into “+” values and numbers for statistical purposes. The semi-quantitative method and scoring system levels used in this research are well established and were widely used in previous morphological studies for several decades [ 26 , 27 ], and are still used and accepted in recent publications [ 28 , 29 ]. The appearance of positive structures was recorded using a semi-quantitative method where: 0—no positive structures in the visual field; 0/+—occasional positive structures in the visual field; +—few positive structures; ++—a moderate number of positive structures; +++—numerous positive structures; ++++—abundant positive structures in the visual field [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, there are limited data on its role in human cholesteatoma. Our previous studies suggest that HβD-4 is less expressed in human cholesteatoma than HβD-2 [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is scarce information about the role of SHH in cholesteatoma development. Our previous studies showed up-regulation of the SHH gene protein in pediatric and adult cholesteatoma cases compared with control skin [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of cholesteatoma has not been fully understood. Scholars have been studying different molecular changes in recent years, including variation, [ 2 ] apoptosis, inflammation, infection, [ 3 ] osteolysis, lipid metabolism, and neovascularization. People discovered that the significance of numerous proteolytic enzymes should not be overlooked while investigating the damage mechanism of cholesteatoma to surrounding tissues, with MMPs (matrix metalloproteinases) becoming a research hotspot.…”
Section: Introductionmentioning
confidence: 99%